answersLogoWhite

0


Want this question answered?

Be notified when an answer is posted

Add your answer:

Earn +20 pts
Q: What is 3a 6?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

What is 3a - 6 when a equals 3?

(3 x 3) - 6 = 3 3a-6=3 3a=3+6 3a=9 a=9/3 a=3


What is 3a divided by 6 as a fraction in simplest form?

0.5


If a plus b equals 6 what is the value of 3a plus 3b?

If a + b = 6, what is the value of 3a + 3b?


3a 12 plus a 6 Is a Solution Of The Equation?

No. 3a 12 plus a 6 is not a solution Of an equation.


Is 3a 12 plus a 6 a Equation?

Yes. 3a plus 12 plus 6 is an example of an Equation.


What is the value of a in 13a - 6 plus a equals 5a plus 3 plus 3a?

13a - 6 + a = 5a + 3 + 3a 13a + a - 5a - 3a = 3 + 6 6a = 9 6a/6 = 9/6 a = 3/2


How do you do this A x 3 a plus 12?

Simplifying a = 3a + 12 Reorder the terms: a = 12 + 3a Solving a = 12 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. a + -3a = 12 + 3a + -3a Combine like terms: a + -3a = -2a -2a = 12 + 3a + -3a Combine like terms: 3a + -3a = 0 -2a = 12 + 0 -2a = 12 Divide each side by '-2'. a = -6 Simplifying a = -6


How do you solve 1a-12a-69 3a?

a-1<2a-6<9+3a


If 3a - 9 equals 6 what is the value of 4a - 1?

3a-9 = 6 3a = 6+9 3a = 15 a = 15/3 a = 5 Substitute a = 5 into 4a-1. 4a-1 =4(5)-1 =20-1 =19 Therefore, the value of 4a-1 is 19.


Is 6-3a equals 3a-6 equivalent?

No they are not equivalent, commutative property applies to addition, not subtraction. The two expressions will be equal only if a = 2, in which case you will have 6-6 = 6-6 = 0


3a and gt -6?

a .gt. -3


What is the simplified form of a over 3 all over 6 over 3 a?

It sounds like you're saying: (a/3) / (6/3a) Multiply numerator by inverse of denominator. = (a/3)*(3a/6) Collect products. = (3a^2) / 18 Factor out 3. = (a^2)/6 Final answer.